2009
DOI: 10.1103/physreva.80.032104
|View full text |Cite
|
Sign up to set email alerts
|

Bell-inequality test for spatial-mode entanglement of a single massive particle

Abstract: Experiments violating Bell inequalities have formed our belief that the world at its smallest is genuinely non-local. While many non-locality experiments use the first quantised picture, the physics of fields of indistinguishable particles is captured most conveniently by second quantisation. This implies the possibility of non-local correlations, such as entanglement, between modes of the field. In this paper, we propose an experimental scheme that tests the theoretically predicted entanglement between modes … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 39 publications
0
28
0
Order By: Relevance
“…Recently, particle-number nonconserving superpositions have attracted renewed interest in the context of cold atoms. It was suggested that when the two modes are coupled to a third one containing a Bose-Einstein condensate that forms a "coherent" reservoir, such superpositions might become possible and might have applications for quantum communication [33,34]. Below we will argue that this kind of "naturally occurring" entanglement is very useful for precision measurements.…”
Section: A Different Physical Realizations Of a Beam Splittermentioning
confidence: 94%
See 1 more Smart Citation
“…Recently, particle-number nonconserving superpositions have attracted renewed interest in the context of cold atoms. It was suggested that when the two modes are coupled to a third one containing a Bose-Einstein condensate that forms a "coherent" reservoir, such superpositions might become possible and might have applications for quantum communication [33,34]. Below we will argue that this kind of "naturally occurring" entanglement is very useful for precision measurements.…”
Section: A Different Physical Realizations Of a Beam Splittermentioning
confidence: 94%
“…For laser light in a coherent state with N 1 or even the most squeezed states currently available [54,55], the fluctuations of N still satisfy σ (N )/N 1, and the average photon number is therefore representative of the photon number in any realization. A state of the form (33) with N K/2 maximizes the photon-number fluctuations, however, and obviously the average value of N is never realized (only N = 0 or N = K are). Nevertheless, the scaling with N is highly relevant practically, as it corresponds to the mean energy in the state, which is indeed what makes producing the state costly.…”
Section: B One-mode Statesmentioning
confidence: 99%
“…However, to reliably confirm spatial-mode entanglement of a single massive particle in an experiment, one would have to ensure that no additional * l.heaney1@physics.ox.ac.uk entanglement entered the system via the particle reservoir (see [23,24] for further discussion of this point) and even if this were guaranteed, such a coupling to the reservoir is likely to be difficult to implement under realistic conditions. Moreover, both in the photon experiment [15] and in theoretical proposals [9,21], a local postselection of the measurement outcomes was required to see a violation of the CHSH inequality, which meant that these tests only strictly probed for entanglement (i.e., the Bell inequality was used as an entanglement witness [25]), and not the more stringent property of nonlocality.…”
Section: Introductionmentioning
confidence: 99%
“…However, schemes to detect single particle and/or spatial entanglement unambiguously continue to be devised and attempted, e.g. [21][22][23][24][25], but are so far probably not free of loopholes.…”
Section: Introductionmentioning
confidence: 99%